2014
DOI: 10.1007/s11357-014-9635-2
|View full text |Cite
|
Sign up to set email alerts
|

WNT3A gene polymorphisms are associated with bone mineral density variation in postmenopausal mestizo women of an urban Mexican population: findings of a pathway-based high-density single nucleotide screening

Abstract: Osteoporosis (OP) is a common skeletal disorder characterized by low bone mineral density (BMD) and is a common health problem in Mexico. To date, few genes affecting BMD variation in the Mexican population have been identified. The aim of this study was to investigate the association of single nucleotide polymorphisms (SNPs) located in genes of the Wnt pathway with BMD variation at various skeletal sites in a cohort of postmenopausal Mexican women. A total of 121 SNPs in or near 15 Wnt signaling pathway genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…67 Furthermore, LRP6 rs1181334 was also associated with decreased total hip BMD (P = 0.014) in 425 postmenopausal woman of an urban Mexican population. 68 These data support previously reported associations of LRP6 with BMD. 69 In the past years, it has been established that LRP6 controls osteoblast differentiation in mice models.…”
Section: Lrp6 Genetic Polymorphisms and Osteoporosissupporting
confidence: 91%
“…67 Furthermore, LRP6 rs1181334 was also associated with decreased total hip BMD (P = 0.014) in 425 postmenopausal woman of an urban Mexican population. 68 These data support previously reported associations of LRP6 with BMD. 69 In the past years, it has been established that LRP6 controls osteoblast differentiation in mice models.…”
Section: Lrp6 Genetic Polymorphisms and Osteoporosissupporting
confidence: 91%
“…The GoldenGate BeadArray (Illumina) was used to genotype a set of 96 AIMs distributed across the genome. These AIMs have been validated in other studies of the Mexican population to primarily distinguish between the American, European and African populations [30, 31]. …”
Section: Subjects and Metodsmentioning
confidence: 99%
“…Previous studies have identified a number of recessive genes influencing osteoporosis, including VDR, (49) LRP5 , (22) and WNT3A , (24) et al We examined associations of ROHs including these recessive genes with BMD and fractures in our study. We confirmed several recessive genes at the replication level.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis could be affected by recessive loci. (2224) For instance, variation in WNT3A was strongly associated with hip BMD under the recessive model. (24) SNP rs312009 in the 5′-flanking region of LRP5 was associated with BMD under the recessive model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation